Analisis Sistem dan Prosedur Penerimaan Pendapatan Asli Daerah (PAD) Pada Badan Pengelolaan Pajak Dan Retribusi Daerah Kota Medan - Zulhamidah Zulhamidah; Juliana Nasution (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2022)
This study aims to find out how the system and procedures for receiving local revenue are carried out at the Regional Financial and Asset Management Agency of Palembang City. Systems and procedures are stages or revenue streams from data collection to data processing with regional financial management guidelines and government regulations applied so that they can be assessed whether they are appropriate or not.The data that are managed in this study are the systems and procedures for receiving original local revenue that are in the financial management agency and the regional assets of Palembang. Data analysis and discussion were carried out with a descriptive qualitative analysis method, namely by collecting and analyzing theories from various sources and experts as literature, so that these theories were linked to applications that have been applied to the Regional Financial and Asset Management Agency of Palembang City in the admission process